L’impacte de la violence et de l’agressivité sur la relation soignant-soigné au service des urgences médicaux chirurgicales.: Etude pratique au service de l’urgence médicale chirurgicale de CHU Tlemcen - Guellil, Mohammed Réda (Journal of Human Sciences, 2022)
The present study aimed at describing the effects of violence and aggressiveness on the relation nurse-patient within the medico-surgical emergency.This is an exploratory study on which we applied the analytical and descriptive approach so as to reach the objectives of the study and collect the data that approve the accuracy this research which used two different types of tools of research; case study and the questionnaire for the nursing staff, and the grid of interview for the patients.After analysing and interpreting the findings, the study showed a set of results which approve its hypotheses; the main ones are: both aggressiveness and violence settle out direct effects on the relational frame between the nurse and patients. Besides, violence towards the nurse staff generates professional errors, inattention, and a decrease or an alteration of relational capacities within emergency services.